Adherence to patient selection criteria in patients undergoing transcatheter aortic valve implantation with the 18F CoreValve ReValving System. Issue 1 (10th September 2009) - Piazza, N; Otten, A; Schultz, C; Onuma, Y; Garcia-Garcia, H M; Boersma, E; de Jaegere, P; Serruys, P W
Abstract : Background: Anecdotal evidence suggests that transcatheter aortic valve implantation (TAVI) is being used beyond pre-market label indications. Methods: To assess the frequency and outcomes associated with "off-label" use of TAVI, we conducted a retrospective study, examining adherence to patient selection criteria in 63 patients undergoing implantation with the 18F CoreValve ReValving System (CRS). Label status (on-label vs off-label) was determined by following (1) inclusion/exclusion criteria indicated in the 18F CRS safety and efficacy trial and (2) a patient selection matrix indicating anatomical boundaries to guide patient selection. Off-label use was defined as the presence of at least one exclusion criterion or "non-acceptable" criteria based on the patient selection matrix. Results: Off-label implantation was identified in 42 patients (67%)—40% had one, 19% had two and 8% had three or more off-label criteria. Baseline demographics were similar between the groups except for a higher logistic EuroSCORE in the on-label group (19.8 (11.2) vs 14.5 (7.3), p = 0.029). There was no significant difference in the procedural success rates between the on-label and off-label groups (91% vs 95%, respectively, p = 0.47). The frequency of angiographic moderate-severe aortic regurgitation, post-implant dilatation or implantation of a second valve was also similar between the groups. At 30 days, the cumulative death rate was 10%; there were four deaths in the "on-label" and three deaths in the "off-label" group. Conclusion: In this study we found that "off-label" implantation of the CRS was common. Further studies are needed to evaluate the consequences of "label status" for patients undergoing TAVI.